Comparing IV with structural models: what simple IV can and cannot identify - James Joseph Heckman; Sergio Urzúa (Institute for the Study of Labor (IZA), 2009)
This paper compares the economic questions addressed by instrumental variables estimators with those addressed by structural approaches. We discuss Marschak's Maxim: estimators should be selected on the basis of their ability to answer well-posed economic problems with minimal assumptions. A key identifying assumption that allows structural methods to be more informative than IV can be tested with data and does not have to be imposed.
urn:nbn:de:101:1-20090210196
Keywords: C31; 330; Instrumental variables; structural approaches; Marschak's Maxim; Instrumentalvariablen-Schätzmethode; Strukturgleichungsmodell; Schätztheorie; Vergleich